L'intégration du genre dans la lutte aux changements climatiques au Québec - Rochette, Annie (Service aux collectivités de l'UQAM/Réseau des femmes en environnement, 2013)
Ce rapport rend compte d'une recherche qui visait à identifier les enjeux et préoccupations des Québécoises quant aux changements climatiques, bâtir un argumentaire sur l'importance des liens entre le genre et les changements climatiques et consolider un réseau de collaboration et d'action politique sur cette problématique, réunissant des groupes de femmes, des groupes environnementaux et des personnes en position de prendre des décisions.
Keywords: 2000 à aujourd'hui; 2010-2019; LGBTQIA2+; SAC; amériques; environnement; genre; identités LGBTQIA2+; militance; projet charge mentale; périodes historiques; québec; rapport; recherche partenariale; ressource en ligne; régions géographiques; thématiques

Geographies of privilege - Twine, France Winddance; Gardener, Bradley (Routledge, 2013)
How are social inequalities experienced, reproduced and challenged in local, global and transnational spaces? What role does the control of space play in distribution of crucial resources and forms of capital (housing, education, pleasure, leisure, social relationships)? The case studies in Geographies of Privilege demonstrate how power operates and is activated within local, national, and global networks. Twine and Gardener have put together a collection that analyzes how the centrality of spaces (domestic, institutional, leisure, educational) are central to the production, maintenance and transformation of inequalities. The collected readings show how power--in the form of economic, social, symbolic, and cultural capital--is employed and experienced. The volume's contributors take the reader to diverse sites, including brothels, blues clubs, dance clubs, elite schools, detention centers, advocacy organizations, and public sidewalks in Canada, Italy, Spain, United Arab Emirates, Mozambique, South Africa, and the United States. Geographies of Privilege is the perfect teaching tool for courses on social problems, race, class and gender in Geography, Sociology and Anthropology.
Keywords: afrique; afrique du sud; amériques; anthropologie; approches et analyses; canada; classe sociale; discipline; environnement; espagne; europe; géographie; italie; mozambique; outils; ouvrages de références; privilèges; racisme; régions géographiques; sciences humaines; sexisme; sociologie; systèmes d'oppressions; thématiques; émirats arabes unis; états-unis